Roetemerker begeleiding as deel van missionale gemeentes - Johannes C. Avenant (Verbum et Ecclesia)
Milestones guidance as part of missional congregations. This article highlights the importance of establishing and celebrating milestones in the challenges of integrating and retaining children and adolescents within the church. The research clearly showed that congregations often fall short in effectively guiding baptised children and adolescents to become integral members of their faith communities. Furthermore, it highlights that the strong emphasis on confirmation, with its strong knowledge focus, creates the impression that this milestone marks the endpoint of the faith formation journey rather than an element of ongoing discipleship within a missional church. This perspective therefore limits the development of a missional congregational identity. This article argues that a reappraisal of biblical teaching fundamentals and faith formation will not only enhance the integration of children and adolescents into the church, but also guide them towards active participation in the church’s missional ministry. Faith formation signifies initiation, guidance and discernment on a lifelong discipleship journey. Along this journey, establishing, guiding, and celebrating milestones serve as continues and focused faith formation through a process of orientation, identification, profession of faith, and confirmation. It is consistently highlighted that this formation of faith inevitably includes the discovery of and participation in the missional identity of the church.